Multi-Transcript Level Profiling Revealed Distinct mRNA, miRNA, and tRNA-Derived Fragment Bio-Signatures for Coping Behavior Linked Haplotypes in HPA Axis and Limbic System - Gley, Kevin; Hadlich, Frieder; Trakooljul, Nares; Haack, Fiete; Murani, Eduard; Gimsa, Ulrike; Wimmers, Klaus; Ponsuksili, Siriluck (Frontiers in Genetics, 2021)
The molecular basis of porcine coping behavior (CB) relies on a sophisticated interplay of genetic and epigenetic features. Deep sequencing technologies allowed the identification of a plethora of new regulatory small non-coding RNA (sncRNA). We characterized mRNA and sncRNA profiles of central parts of the physiological stress response system including amygdala, hippocampus, hypothalamus and adrenal gland using systems biology for integration. Therefore, ten each of high- (HR) and low- (LR) reactive pigs (n = 20) carrying a CB associated haplotype in a prominent QTL-region on SSC12 were selected for mRNA and sncRNA expression profiling. The molecular markers related to the LR group included ATP1B2, MPDU1, miR-19b-5p, let-7g-5p and 5’-tiRNALeu in the adrenal gland, miR-194a-5p, miR-125a-5p, miR-7-1-5p and miR-107-5p in the hippocampus and CBL and PVRL1 in the hypothalamus. Interestingly, amygdalae of the LR group showed 5’-tiRNA and 5’-tRF (5'-tRFLys, 5'-tiRNALys, 5'-tiRNACys and 5'-tiRNAGln) enrichment. Contrarily, molecular markers associated with the HR group encompassed miR-26b-5p, tRNAArg, tRNAGlyiF in the adrenal gland, IGF1 and APOD in the amygdala and PBX1, TOB1 and C18orf1 in the hippocampus and miR-24 in the hypothalamus. In addition, hypothalami of the HR group were characterized by 3'-tiRNA enrichment (3'-tiRNAGln, 3'-tiRNAAsn, 3'-tiRNAVal, 3'-tRFPro, 3'-tiRNACys and 3'-tiRNAAla) and 3’-tRFs enrichment (3'-tRFAsn, 3'-tRFGlu and 3'-tRFVal). These evidence suggest that tRNA-derived fragments and their cleavage activity are a specific marker for coping behavior. Data integration revealed new bio-signatures of important molecular interactions on a multi-transcript level in HPA axis and limbic system of pigs carrying a CB-associated haplotype.